2014
DOI: 10.2214/ajr.13.12163
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Flat-Panel CT Arthrography for Cartilage Defect Detection in the Ankle Joint: Comparison With MDCT Arthrography With Gross Anatomy as the Reference Standard

Abstract: Flat-panel CT arthrography is accurate for detecting cartilage defects in the ankle joint and is an alternative to MDCT arthrography that may have better diagnostic performance and may permit the use of a lower radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In most patients, clinical symptoms are nonspecific; and standard radiographs are known to be inaccurate for the evaluation of the articular cartilage status [2]. Because detection of cartilage defects in the ankle joint is crucial for surgical decision-making, many investigators have explored a variety of imaging techniques for assessing the integrity of hyaline cartilage [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most patients, clinical symptoms are nonspecific; and standard radiographs are known to be inaccurate for the evaluation of the articular cartilage status [2]. Because detection of cartilage defects in the ankle joint is crucial for surgical decision-making, many investigators have explored a variety of imaging techniques for assessing the integrity of hyaline cartilage [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Current detector designs in multidetector CT (MDCT) can reach a maximal z-resolution of 0.4-0.5 mm, enabling the detection of small cartilage and bone lesions that could be overlooked in MR arthrography [10,11]. Thus, MDCT arthrography is considered the method of choice in the assessment of articular cartilage, especially in the ankle joint where hyaline cartilage is particularly thin [3,6,7,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 25 years, CT and MR imaging have come to play a greater role in the diagnosis and grading of osteochondral lesions and conventional radiographs are now generally considered to be insensitive for the evaluation of suspected chondral injury, unless there is a significant subjacent osseous component. With the development of slip ring technology and numerous sequential detector rows in CT or multidetector CT, the ability to evaluate subtle osseous injuries with multi-planar reconstructions has improved dramatically 8, 9, 10, 11, 12. We believe that high-resolution MDCT plays a valuable role in the delineation of subchondral lesions that may present with instability of osteochondral fragments at the articular surface by detecting the presence of detachment, fragmentation, and displacement; we recommend MDCT arthrography in the setting of such lesions visible on MR imaging but equivocal for instability.…”
Section: Discussionmentioning
confidence: 99%
“…Kraniotis et al described that CTA detects radiographically silent osteochondral lesions in patients with fractures of the ankle joint but did not compare CTA to other imaging techniques [16]. In the study by Chemouni et al CT arthrography showed an accuracy of 88% [31]. For detection of retropatellar osteochondral lesions, CTA performed superior compared with conventional MRI in several studies [1, 28].…”
Section: Discussionmentioning
confidence: 99%